Streamed video in an academic library: expectations, challenges and response - Wells, David; Blackwood, Diana (VALA, 2011)
Streamed video is the latest type of content to gain the attention of educators and librarians. This paper examines the take up of this new resource type at Curtin University Library with particular attention to the use of individual streamed titles on the Kanopy platform. It includes reflections on the academic areas which are so far most engaged with streamed video materials, on the particular complexities they present for acquisitions departments, and on usage statistics for the first year of effective operation.